Primary syphilis without chancre – A case report of rare syphilitic balanitis of Follmann - Ren, Xu-qi; Nie, Qun-ling; Liu, An-qi (Frontiers in Medicine, 2022)
Introduction: Syphilitic balanitis of Follmann (SBF) is a rare condition of primary syphilis, which is characterized by any kind of balanitis, with or without chancre on penis, combined with the presence of swollen inguinal lymph nodes and confirmed by the finding of Treponema pallidum in the lesions or by the positive serological syphilitic testing. Identifying the SBF in time is very important in properly treating the disease and stopping the spread of the syphilis. Case Presentation: A 42year-old heterosexual male patient came to our clinic and complained of a painless, hard erythema nodule with whitish scale in his coronal sulcus of penis for about a week. The dermatologic examination revealed an infiltrative, hard erythematous lesion surrounding the coronal sulcus of the patient’s penis, with mild erosion and a small amount of exudation. There was a whitish pseudomembrane-like covering on the surface of the erythematous lesion in coronal sulcus, which is mimicked as candidal balanitis. The result of fungus microscopic examination was negative, while the laboratory findings showed positive results in serologic syphilitic testing. The patient was diagnosed with primary syphilis and treated with a dose of benzylpenicillin 2.4 million units intramuscularly. The patient’s skin lesions disappeared completely 60 days after penicillin treatment. Conclusions: To our knowledge this is the first SBF case reported in China. Syphilitic balanitis of Follmann may have variable clinical appearances. We emphasize that when balanitis with risky sexual activities or with sexually transmitted diseases the diagnosis of SBF should be kept in mind.